USING UAV’S IMAGERY VEGETATION INDICES COMBINATION IN DELINEATION OF SOIL MAP UNITS - Layla A. Abdelelah; Kusay A. Wheib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Alsweira research farm (44.823410 and 44.823040 N, 33.012701 and 33.012090 E) of an area of 5000 Da., was selected to conduct the UAV’s photogrammetry interpretation to delineate and separate soil units at the series level in collaboration with the measured RGB vegetation indices derived from their data. Visual interpretation of mosaic and the vegetation indices efficiently eased the delineation process of soil series map. RGB indices measured form UAV’s imagery were efficient in delineating soil units, and they showed significant relationships with above ground biomass where the later is representing the vegetation cover in the study area. NGRDI, ExG, NExG, and RGBVI showed high correlation with above ground biomass (g m-2) while VARI showed no relationship with it. Percentages of Indices participation in delineation and isolation of map units were as follow: NGRDI> RGBVI > NexG> ExG> VARI in 90%, 89%, 86%, 85%, and 52% respectively.